The Little Data Book on Africa 2007 - World Bank (Washington, DC, 2013)
The little data book on Africa 2007 is a pocket edition of Africa Development Indicators 2007. It contains some 100 key indicators on economics, human development, governance, and partnership and is intended as a quick reference for users of the Africa Development Indicators 2007 book and African development indicators online. The country tables present the latest available data for World Bank member countries in Africa.